ANALISIS MATERIAL HANDLING PADA PRODUKSI POT BUNGA DI UMKM CV SURYATAMA BETON - Ismi Mashabai Hamzah; Iksan Adiasa; Asni Utari Ramadhani Lasina (Fakultas Teknik Universitas Tulang Bawang Lampung, 2022)
The development of the industrial world is currently growing very rapidly over time, and so is the progress of existing technology. Micro, Small and Medium Enterprises (MSMEs) are economic business activities owned by individuals or groups in accordance with the criteria stipulated by Law no. 20 of 2008. In this case, of course, MSME actors have a superior product that is produced in it. One of the SMEs in Sumbawa by producing a product, namely CV Suryatama Beton. This company produces paving blocks, profile poles, concrete buis, finished mamak, flower pots, iron wire pallets, road pavers, km stakes and wall paving blocks. The number of types of products produced certainly requires a high level of flexibility in machines and production processes. Flexible manufacturing system or FMS (Flexible manufacturing system) is a manufacturing system that can react flexibly to changes. The two kinds of system changes can be changes in the type of product to be produced (machine flexibility), as well as changes in the sequence of processes in the manufacture of these products (routing flexibility). The advantage of using FMS in a mass production system is the high flexibility in allocating time and effort, so as to increase productivity and product quality and reduce production costs. correct equipment and methods. Material handling system planning is an important component in facility planning, especially in relation to layout design.